How to identify common errors in english (Noida : Maple Press)
This Handbook based on common mistakes in English while writing such as word formation wrong use and offers a correct version and explanation that will help students avoid making the same mistakes themselves. Completely updated guide for young writers to reflect modern English usage. It is written for students from intermediate level and above looking to develop natural fluency in their speaking and writing skills.